Factors that influencing individual investment decision on mutual funds : a study in Temerloh / Nur Faezah Zulkifli - Zulkifli, Nur Faezah (Bachelor Of Business Administration (Hons) Marketing, 2015)
Mutual funds is a type of investment security which enables investors to pool their money together in order to diversify their portfolio management. Individual should study in depth about mutual funds in order to make a better decision. The purpose of the study is to identify the relationship between knowledge about investment avenue, risk taking ability and past performance of company stock. Total of 100 questionnaires have been distributed in gathering the relevant information and analyze using SPSS. This study is used descriptive study as a research design. The independent variables used in individual investment decision on mutual funds is knowledge about investment avenue, risk taking ability and past performance of company stock. The finding of this research is knowledge about investment avenue and past performance of company stock has significant relationship with individual investment decision on mutual funds. Meanwhile, risk taking ability has no significant relationship with individual investment decision on mutual funds